Mice lacking collapsin response mediator protein 1 manifest hyperactivity, impaired learning and memory, and impaired prepulse inhibition - Yamashita, Naoya; Takahashi, Aoi; Takao, Keizo; Yamamoto, Toshifumi; Kolattukudy, Pappachan; Miyakawa, Tsuyoshi; Goshima, Yoshio (Frontiers in Behavioral Neuroscience, 2013)
Collapsin response mediator protein 1 (CRMP1) is one of the CRMP family members that are involved in various aspects of neuronal development such as axonal guidance and neuronal migration. Here we provide evidence that crmp1-/- mice exhibited behavioral abnormalities related to schizophrenia. The crmp1-/- mice exhibited hyperactivity and/or impaired emotional behavioral phenotype. These mice also exhibited impaired context-dependent memory and long-term memory retention. Furthermore, crmp1-/- mice exhibited decreased prepulse inhibition, and this phenotype was rescued by administration of chlorpromazine, a typical antipsychotic drug. In addition, in vivo microdialysis revealed that the methamphetamine-induced release of dopamine in prefrontal cortex was exaggerated in crmp1-/- mice, suggesting that enhanced mesocortical dopaminergic transmission contributes to their hyperactivity phenotype. These observations suggest that impairment of CRMP1 function may be involved in the pathogenesis of schizophrenia. We propose that crmp1-/- mouse may model endophenotypes present in this neuropsychiatric disorder.